Senior Non-preferred Bonds as an Instrument to Meet the MREL Requirement - Kozińska, Magdalena (Journal of Finance and Financial Law, 2023)
The purpose of the article is to present the results of the first assessment of the senior non-preferred (SNP) bond market’s development in Poland. SNP bonds were introduced to facilitate meeting the banks’ MREL, which aims to build banks’ loss absorption and recapitalization capacity. At the same time, they are the next source of bank funding. The development of the SNP bond market has been initiated relatively recently with the full establishment of resolution systems and the introduction of the MREL requirement for banks. Although the first non-binding decisions to impose the MREL requirement were issued in 2016, the concept of SNP was formally introduced in 2017. In 2019, an amendment to the rules for determining the MREL requirement was adopted, which was implemented into the Polish legal framework in 2021, and in 2022, an amendment to the regulations on bonds was introduced, enabling the issuance of SNP bonds counted to MREL. Since then (2022), there has been a full legal framework for setting and maintaining the MREL requirement, and therefore full conditions for the development of this market in Poland. Therefore, it is justified to say that this market is relatively young. Moreover, it is under-investigated by scientists. This justifies the assessment of the potential scale of this market, its ability to achieve the goal for which it was created, as well as the premises and barriers to its development. Methodology. The research methods were quantitative analysis (calculation of the potential shortage of the MREL requirement and needs in the field of securities issuance based on reporting data) and qualitative analysis (in terms of assessing the challenges). Results of the research. The main determinant of its potential is the amount of MREL shortfall, which depends on the financial situation of banks and partly on the strategy of resolution authorities (responsible for setting the level of this requirement). The main challenges for the Polish SNP bond market are related to the prospects for further development of the banking sector and its environment (business and strategic). Nevertheless, it seems that the potential of the SNP bond market in Poland is underrated. The article contributes to general knowledge about bank funding sources.